Advances in Human Aspects of Transportation Proceedings of the AHFE 2016 International Conference on Human Factors in Transportation, July 27-31, 2016, Walt Disney World®, Florida, USA - Stanton, Neville A.; Landry, Steven; Di Bucchianico, Giuseppe; Vallicelli, Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses the latest advances in research and development, design, operation and analysis of transportation systems and their complementary infrastructures. It reports on both theories and case studies on road and rail, aviation and maritime transportation. The book covers a wealth of topics, from accident analysis, vehicle intelligent control, and human-error and safety issues to next-generation transportation systems, model-based design methods, simulation and training techniques, and many more. A special emphasis is given to smart technologies and automation in transport, as well as to user-centered, ergonomic and sustainable design of transport systems. The book, which is based on the AHFE 2016 International Conference on Human Factors in Transportation, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, mainly addresses transportation system designers, industrial designers, human-computer interaction researchers, civil and control engineers, as well as vehicle system engineers. Moreover, it represents a timely source of information for transportation policy-makers and social scientists dealing with traffic safety, management, and sustainability issues in transport.
Road and Rail - Ergonomic Analysis and Assistance -- Aviation - Human Factors in Aviation -- Road and Rail - Pedestrians and Intersections -- Road and Rail - Driver, Behavior, Distraction and Fatigue -- Maritime - Human Performance and Safety Assessment in the Maritime Domain -- Road and Rail - Vehicle Automation -- Road and Rail - Logistics and Passengers -- Road and Rail - Accidents and Pedestrian Modeling -- Road and Rail - Warning Systems/Public Transport -- Aviation - Human Factors in Aviation -- Road and Rail - Eco-Driving and Electric Vehicles -- Road and Rail - Education and Hazard Perception -- Road and Rail - Infrastructure -- Maritime - Users, Tasks and Tools in the Maritime Domain -- Road and Rail - Safety, Driver Psychophysiology and Eye Tracking.
Keywords: Computational intelligence; Transportation engineering; Traffic engineering; Cognitive psychology; Engineering design; Computational Intelligence; Transportation Technology and Traffic Engineering; Cognitive Psychology; Engineering Design